THE NEED, PRINCIPLE AND SUPPORTS OF THE TRANSITION TO A GREEN ECONOMY: https://doi.org/10.5281/zenodo.14523146 - Boltakov , Sardor; Sattarova , Madina (International scientific and practical conference, 2024)
The process of globalization requires a qualitative renewal of the technological base of industrialized countries, a transition to a modernized economy to a new technological structure that ensures the improvement of the quality of life and living environment, while increasing the level of production efficiency and competitiveness. This article analyzes the problem of limited resources, the need to transition to a green economy, its principles and levers in the territory of Uzbekistan.